Application of IBA PGR Concentration On Germination of Sugarcane (Saccharum Officinarum L) Application of IBA PGR Concentration On Germination of Sugarcane (SaccharumOfficinarum L)Cuttings Bambang Wicaksono Hariyadi , Sri Purwanti Cuttings - Bambang Wicaksono Hariyadi; Sri Purwanti (Faculty of Agriculture, Merdeka University Surabaya, 2017)
The purpose of this study is to determine the effect of IBA plant growth regulators (Indole Butyric Acid)on germination of sugarcane cuttings (Saccharwn o_mcinarum L). The experimental materials include PSJT 941 variety of sugarcane cuttings, soil and manure as medium with 2: 1 ratio. IBA and 50% alcohol is used as treatment. Pest and disease controls used Basudin 60 EC and Dithane M-45. This study uses Randomized Block Design (RAK) with three replicates and each replicate consisted of 2 sample plants. The treatment is as follows: Ko: without treatment, K1: 500 ppm, K2: 1000 ppm, K3: 1500 ppm, K4: 2000 ppm. The study reveals that treatment of K4 IBA solution (2000 ppm)has very significant effect on variables of germination speed, shoot length, number of leaves and number of roots, and significantly different at root length. Administration of IBA solution at concentration of 1500 ppm accelerated germination time of sugar cane cuttings, occurred on the fourth day (fourth). Administration of IBA solution at 2000 ppm gave the highest result which was not different with 1500 ppm concentration on shoot length, leaf number, root length and root number. The higher the concentration of IBA, the higher the shoot length, the number of leaves, the length of the roots and the number of roots of sugar cane produced.